Application of STATCOM to improve the LVRT of DFIG during DC-link capacitor failure - Abdou, A.; Abu-Siada, Ahmed; Pota, H. (Faculty of Engineering, Alexandria University, 2012)
In doubly fed induction generator (DFIG) based wind energy conversion systems (WECS), the DFIG is interfaced to the AC network through grid side voltage source converter (GSC) and rotor side voltage source converter (RSC). The RSC and the GSC are coupled by a DC-link capacitor. The capacitor is used as an energy storage device and is controlled to keep the voltage fluctuation across the DC-link within permissible limits. The sensitivity of DFIG to external faults has motivated researchers to investigate the impact of various grid disturbances such as voltage sag and short circuit faults on the low voltage ride through (LVRT) capability of the DFIG. There is however, a little attention in the literature has been given to investigate the impact of internal faults on the LVRT of the DFIG-based WECS. In this paper, the impact of a DC-link capacitor short circuit fault on the dynamic performance of DFIG-based WECS is investigated. A proper voltage controller for a STATCOM to mitigate the effects of such failure on the voltage profile at the point of common coupling (PCC) is proposed. To examine the robustness of the proposed controller, DFIG compliance with various recently released LVRT grid codes under DC-link failure with and without the STATCOM is investigated and compared. Simulation results indicate that fault has a severe impact on the DFIG voltage profile and the proposed controller is capable of bringing the voltage profile at the PCC to the nominal steady state level.